Ruthenium-based composite nano material and preparation method and application thereof

By using amorphous ruthenium nanosheets to support Pd, Pt, Ir, or Rh nanoclusters in ruthenium-based composite nanomaterials in the anode of AEMFC, the problems of slow reaction kinetics of Pt-based catalysts and easy deactivation of Pd-based catalysts were solved, achieving efficient hydrogenation reaction and resistance to CO poisoning.

CN121307066APending Publication Date: 2026-01-09HANGZHOU VOCATIONAL & TECHN COLLEGE
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511692948.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-11-18
Publication Date
2026-01-09

AI Technical Summary

Technical Problem

Existing Pt-based catalysts exhibit slow reaction kinetics and are sensitive to CO in AEMFC anodes, Pd-based catalysts are prone to deactivation in alkaline media, Ru catalysts lack stability, and heterostructure electrocatalysts regulated by interface engineering have limited controllability.

Method used

Amorphous ruthenium nanosheets are used as supports to load Pd, Pt, Ir, or Rh nanoclusters. The clusters are fixed through strong interactions, creating bifunctional catalytic sites, promoting the rapid reaction of H and -OH, and enhancing the catalyst's resistance to poisoning.

Benefits of technology

It improves the reaction efficiency and stability of the catalyst, enhances its resistance to CO poisoning, and optimizes the kinetics of the hydrogenation reaction.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121307066A_ABST
    Figure CN121307066A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of catalysts, in particular to a ruthenium-based composite nanomaterial and a preparation method and application thereof. The strong interaction between the amorphous ruthenium nanosheet carrier and the cluster can effectively fix cluster atoms and prevent the cluster atoms from migrating and agglomerating in the preparation and reaction processes; the existence of a large number of clusters with high activity and high surface atoms is ensured; and the strong interaction creates a bifunctional catalytic site which does not exist on a single metal. H is adsorbed and dissociated on a Pd site,-OH species are adsorbed on an adjacent defect-rich Ru site, and then the H and the-OH species quickly react at an interface to generate water, so that the efficiency is greatly improved. In addition, the introduction of the amorphous ruthenium nanosheets can promote the oxidation of carbon monoxide on the surface metal clusters, thereby enhancing the anti-poisoning ability of the catalyst.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of catalyst technology, specifically to a ruthenium-based composite nanomaterial, its preparation method, and its application. Background Technology

[0002] The information disclosed in this background section is intended only to enhance understanding of the overall background of the invention and is not necessarily to be construed as an admission or in any way implying that such information constitutes prior art known to those skilled in the art.

[0003] The widespread use of hydrogen energy can effectively reduce dependence on fossil fuels and also reduce environmental pollution from fossil fuel combustion emissions. In hydrogen energy utilization technologies, anion exchange membrane fuel cells (AEMFCs) play a crucial role in efficient hydrogen conversion, with the hydrogen oxidation reaction (HOR) being a key anode reaction in AEMFCs. Therefore, an increasing number of researchers are designing and preparing catalysts for the hydrogen oxidation reaction.

[0004] To date, platinum (Pt)-based catalysts are the most effective hydrogenation catalysts reported. However, their application in AEMFC anodes faces the following challenges: Pt-based catalysts exhibit strong H adsorption, resulting in slow reaction kinetics in alkaline media; they are also exceptionally sensitive to trace amounts of CO in hydrogen, as Pt has a significant adsorption affinity for CO, leading to deactivation of the Pt-based catalyst.

[0005] Palladium (Pd) belongs to the same group as Pt and has a similar electronic structure, thus it also possesses a certain catalytic ability for hydrogen oxidation reactions. However, due to its excessively strong H adsorption, its surface may be covered by excessively strong H adsorbed species during the catalytic process, hindering subsequent reaction steps and causing the active site to be "poisoned," thereby limiting its intrinsic activity.

[0006] Ruthenium (Ru) has similar physicochemical properties to Pt and is less expensive. In addition, studies have shown that Ru has better intrinsic activity than Pt in alkaline hydroxide reactions, but its stability is insufficient. The main reason is that Ru surface is prone to excessive adsorption of -OH, which leads to the active sites being covered and deactivated.

[0007] Heterogeneous electrocatalysts regulated by interface engineering are commonly used in hydrogenation reactions. However, their precision and effectiveness are greatly limited by the bulk properties of the support. Clusters are tiny aggregates of several to hundreds of atoms, typically around 2 nanometers in size. At this scale, most atoms are exposed on the material surface. High surface energy directly leads to high chemical reactivity, but clusters are very prone to aggregation during synthesis and application. Summary of the Invention

[0008] To overcome the above problems, this invention provides a ruthenium-based composite nanomaterial, its preparation method, and its application.

[0009] To achieve the above technical objectives, the present invention adopts the following technical solution: In a first aspect, the present invention provides a ruthenium-based composite nanomaterial, which uses amorphous ruthenium nanosheets as a carrier to load metal nanoclusters; The metal is Pd, Pt, Ir or Rh.

[0010] In one or more embodiments, the proportion of metal nanoclusters is 0.5 wt%-30 wt% based on the total mass of the ruthenium-based composite nanomaterial.

[0011] In one or more embodiments, the size of the metal nanoclusters is 2 to 5 nm.

[0012] A second aspect of the present invention provides a method for preparing the ruthenium-based composite nanomaterial described in the first aspect, comprising the following steps: (1) Disperse ruthenium acetylacetone salt and potassium bromide in an aqueous ethanol solution, mix them evenly, and then remove the solvent to obtain the precursor material; (2) After calcining the precursor material in an oxygen-containing environment, it was kept warm in a hydrogen-argon mixed gas, washed, frozen in liquid nitrogen and freeze-dried to obtain amorphous ruthenium nanosheets; (3) Amorphous ruthenium nanosheets are dispersed in ethylene glycol solution, salts containing Pd, Pt, Ir or Rh are added, and after mixing evenly, heat treatment is performed. The solid is collected by solid-liquid separation, washed, frozen in liquid nitrogen and freeze-dried to obtain ruthenium-based composite nanomaterials.

[0013] In one or more embodiments, in step (1), the molar ratio of ruthenium acetylacetonate to potassium bromide is 1:(6~8).

[0014] In one or more embodiments, in step (1), the volume ratio of ethanol to water in the ethanol-water solution is (6~8):1.

[0015] In one or more embodiments, in step (1), the concentration of ruthenium acetylacetonate in the aqueous ethanol solution is 6-8 mmol / L.

[0016] In one or more embodiments, in step (1), the temperature during solvent removal is 40~50 °C.

[0017] In one or more embodiments, in step (2), the aerobic environment is air.

[0018] In one or more embodiments, in step (2), the calcination temperature is 260~350 °C, and the calcination time is 1-4 h. The calcination temperature should be above the melting point of ruthenium acetylacetonate and below the melting point of alkali metal salts. However, if the temperature is too high, crystalline ruthenium will be formed. Therefore, the calcination temperature is limited to 260~350 °C.

[0019] In one or more embodiments, in step (2), the volume fraction of hydrogen in the hydrogen-argon mixture is 8-12%, preferably 10%.

[0020] In one or more embodiments, in step (2), the temperature for heat preservation is 100~200 ℃ and the heat preservation time is 0.5~2 h.

[0021] In one or more embodiments, in step (2), the liquid nitrogen freezing time is 2 to 10 minutes.

[0022] In one or more embodiments, in step (2), the freeze-drying time is 8 to 24 hours.

[0023] In one or more embodiments, in step (3), the temperature of the heat treatment is 75~200 ℃; the time of the heat treatment is 1~12 h.

[0024] In one or more embodiments, in step (3), the liquid nitrogen freezing time is 2 to 10 minutes.

[0025] In one or more embodiments, in step (3), the freeze-drying time is 8 to 24 hours.

[0026] A third aspect of the present invention provides the application of the ruthenium-based composite nanomaterials described in the first aspect or the ruthenium-based composite nanomaterials prepared by the preparation method described in the second aspect in the catalysis of hydrogen oxidation in an alkaline environment.

[0027] In a fourth aspect, the present invention provides a fuel cell comprising a cathode, an anode, and a membrane, wherein the anode comprises the ruthenium-based composite nanomaterial described in the first aspect or the ruthenium-based composite nanomaterial prepared by the preparation method described in the second aspect.

[0028] The beneficial effects of this invention are as follows: The strong interaction between the amorphous ruthenium nanosheet support and the clusters effectively immobilizes the cluster atoms, preventing their migration and aggregation during preparation and reaction. This ensures the presence of a large number of highly active clusters with high surface area. Furthermore, this strong interaction creates bifunctional catalytic sites that are not found on single metals. H adsorbs and dissociates at Pd sites, while -OH species adsorb at adjacent, defect-rich Ru sites, and then the two react rapidly at the interface to generate water, greatly improving efficiency. In addition, the amorphous ruthenium nanosheets can also promote the oxidation of carbon monoxide on its surface metal clusters, thereby enhancing the catalyst's resistance to poisoning. Attached Figure Description

[0029] The accompanying drawings, which form part of this invention, are used to provide a further understanding of the invention. The illustrative embodiments of the invention and their descriptions are used to explain the invention and do not constitute an improper limitation of the invention.

[0030] Figure 1 X-ray diffraction patterns of palladium nanoclusters / amorphous ruthenium nanosheets and amorphous ruthenium nanosheets; Figure 2 Images a and b in the image are transmission electron microscopy (TEM) images of amorphous ruthenium nanosheets. Figure 3 Images a and b in the image are transmission electron microscopy (TEM) images of palladium nanoclusters / amorphous ruthenium nanosheets. Figure 4 Energy-scattered X-ray spectra (EDS) of palladium nanoclusters / amorphous ruthenium nanosheets; Figure 5 The alkaline hydroxide LSV curves of the samples in Example 1, Comparative Example 1, and Comparative Example 2 are shown. Figure 6 The hydrogenation stability test curve of palladium nanoclusters / amorphous ruthenium nanosheets prepared in Example 1 after 160 h is shown. Figure 7 The results of the CO toxicity test on the hydroxide reaction of the samples in Example 1 and Comparative Example 2 in 0.1 M KOH (saturated H2 / 1000 ppm CO) solution are shown. Detailed Implementation

[0031] It should be noted that the following detailed descriptions are exemplary and intended to provide further illustration of the invention. Unless otherwise specified, all technical and scientific terms used in this invention have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains.

[0032] It should be noted that the terminology used herein is for the purpose of describing particular embodiments only and is not intended to limit the scope of exemplary embodiments according to the invention. As used herein, the singular form is intended to include the plural form as well, unless the context clearly indicates otherwise. Furthermore, it should be understood that when the terms "comprising" and / or "including" are used in this specification, they indicate the presence of features, steps, operations, devices, components, and / or combinations thereof.

[0033] In alkaline hydroxide reactions, the rate of hydroxide oxidation is often limited by the adsorption of -OH and its coupling with H. In an alkaline environment, Pd-based catalysts exhibit strong H adsorption, while Ru exhibits strong -OH adsorption; therefore, combining the two can enhance the rate of the hydroxide reaction.

[0034] Interface-engineered heterogeneous electrocatalysts are commonly used in hydrogenation reactions. However, their precision and effectiveness are limited by the bulk properties of the support. Clusters are tiny aggregates of several to hundreds of atoms, typically around 2 nanometers in size. At this scale, most atoms are exposed on the material surface; high surface energy directly leads to high chemical reactivity, but clusters are very prone to aggregation during synthesis and application. To address the problem of easy aggregation of nanoclusters formed by Pd-based catalysts, this invention provides a ruthenium-based composite nanomaterial, which uses amorphous ruthenium nanosheets as a support to load metal nanoclusters; the metal is Pd, Pt, Ir, or Rh.

[0035] Compared to crystalline materials, amorphous ruthenium nanosheets possess a large number of long-range disordered structures, dangling bonds, and low-coordination sites. These sites not only act as extremely low-energy "traps," strongly capturing metal precursors or nucleated nanoclusters and effectively preventing their migration and aggregation during preparation or reaction, but they also serve as highly reactive reaction sites, effectively activating water molecules or hydroxyl species. This is crucial for promoting the electrochemical adsorption (Volmer) step of the hydroxide reaction in alkaline environments. Furthermore, amorphous structures typically exhibit stronger oxyphilicity, enabling more efficient adsorption of -OH species. In alkaline hydroxide reactions, the rate of the hydroxide reaction is often limited by the adsorption of -OH and its coupling with H. Therefore, enhanced -OH adsorption directly promotes reaction kinetics.

[0036] Ruthenium-based composite nanomaterials are heterostructures of clusters / amorphous ruthenium nanosheets. These heterostructures exhibit synergistic electronic effects. For example, in the Pd nanocluster / amorphous ruthenium nanosheet heterostructure, electrons are transferred from Pd to Ru. According to the electronegativity rule (Pd: 2.20, Ru: 2.20, but Ru exhibits greater electronegativity under specific conditions, especially when paired with Pd), electrons from the Pd nanoclusters are likely to be partially transferred to the amorphous Ru nanosheet support. This electronic rearrangement reduces the d-band center of Pd. For the hydrogen oxidation reaction, excessively strong or weak hydrogen binding energies are not conducive to catalysis. Pd itself has a strong adsorption capacity for H, and electron loss moderately weakens the strength of the Pd-H bond, bringing it closer to the optimal value, thereby accelerating the hydrogen desorption step, which is usually the rate-determining step of the hydrogen oxidation reaction.

[0037] The strong interaction between the amorphous ruthenium nanosheet support and the clusters effectively immobilizes the cluster atoms, preventing their migration and aggregation during preparation and reaction. This ensures the presence of a large number of highly active clusters with high surface area atoms. Furthermore, this strong interaction creates bifunctional catalytic sites that do not exist on single metals. H adsorbs and dissociates at Pd sites, while -OH species adsorb at adjacent, defect-rich Ru sites. The two then react rapidly at the interface to generate water, greatly improving efficiency.

[0038] Loading nanoclusters, rather than large particles, onto ruthenium nanosheets maximizes the interfacial perimeter between the clusters and the Ru support. These interfaces are the core regions for synergistic catalysis. Furthermore, the atomic structural mismatch between the clusters and the amorphous Ru substrate may introduce strain into the cluster lattice, thereby altering its electronic structure and further optimizing its adsorption performance.

[0039] Furthermore, the introduction of amorphous ruthenium nanosheets can also promote the oxidation of carbon monoxide on its surface metal clusters, thereby enhancing the catalyst's resistance to poisoning.

[0040] To enable those skilled in the art to better understand the technical solution of the present invention, the technical solution of the present invention will be described in detail below with reference to specific embodiments.

[0041] Example 1 (1) 160 mg of ruthenium acetylacetonate and 340 mg of potassium bromide were dispersed in an ethanol aqueous solution, which was prepared by mixing 50 mL of ethanol and 7 mL of deionized water; the dispersion was formed by ultrasonic treatment. The dispersion was stirred in a water bath at 45 °C and dried to remove the solvent, and the precursor material was obtained.

[0042] (2) The precursor material was heated to 280 °C at a rate of 5 °C / min in air and calcined at this temperature for 1.5 h. After calcination, the temperature was lowered to 120 °C at a rate of 10 °C / min, the gas atmosphere was switched to an argon-hydrogen mixture (hydrogen gas fraction of 10%), and the mixture was held at 120 °C for 1 h. Finally, heating was stopped, and the sample was allowed to cool naturally to room temperature in this atmosphere. The product was washed with ethanol and deionized water, respectively. The washed sample was placed in liquid nitrogen and frozen for 10 min. After being taken out, it was freeze-dried in a freeze dryer for 24 h to obtain amorphous ruthenium nanosheets (abbreviated as Ru NS).

[0043] (3) 10 mg of amorphous ruthenium nanosheets and 5.5 mg of potassium chloropalladate were dispersed in 25 mL of ethylene glycol and sonicated in an ice bath for 20 min to form a uniform dispersion. Subsequently, the dispersion was transferred to an oil bath at 80 °C and stirred continuously (600 r / min) for 2 h. After the reaction was completed, the mixture was centrifuged and the solid was collected. The obtained solid product was washed three times by centrifugation with deionized water. Finally, the washed sample was placed in liquid nitrogen and frozen for 10 min. After being taken out, it was freeze-dried in a freeze dryer for 24 h to obtain ruthenium-based composite nanomaterials, namely palladium nanoclusters / amorphous ruthenium nanosheets, abbreviated as Pd / Ru NS.

[0044] Figure 1 X-ray diffraction patterns of palladium nanoclusters / amorphous ruthenium nanosheets, from Figure 1 As can be seen, no diffraction peaks of crystalline ruthenium were detected in the amorphous ruthenium nanosheets, indicating that ruthenium atoms did not aggregate to form crystals. The presence of broadened peaks of palladium in Pd / Ru NS indicates that the palladium grain size is extremely small.

[0045] Figure 2 The image shows a transmission electron microscope (TEM) image of amorphous ruthenium nanosheets, which reveals that the ruthenium nanosheets exhibit a distinctly amorphous state.

[0046] Figure 3 The image shows a transmission electron microscope (TEM) image of palladium nanoclusters / amorphous ruthenium nanosheets. It can be seen that the palladium nanoclusters are about 2-5 nm in size and are uniformly dispersed on the surface of the amorphous ruthenium nanosheets.

[0047] Figure 4 Energy-scattered X-ray spectroscopy (EDS) of palladium nanoclusters / amorphous ruthenium nanosheets, from Figure 6 As can be seen, the mass fraction of palladium in palladium nanoclusters / amorphous ruthenium nanosheets is 3.8%, and the mass fraction of ruthenium is 96.2%.

[0048] Comparative Example 1 The difference from Example 1 is that the final material is only amorphous ruthenium nanosheets Ru NS.

[0049] Comparative Example 2 The difference from Example 1 is that palladium nanoclusters are modified onto carbon black (Pd / CB).

[0050] Example 2 Before electrochemical testing, the glassy carbon electrode was continuously polished with alumina powder with a particle size of 50 nm, and then cleaned with ethanol and water to obtain a clean surface. 2 mg of catalyst sample was ultrasonically mixed with 0.49 mL of ethanol and 10 μL of Nafion (5% by mass) solution to form a homogeneous slurry. The slurry was then drop-coated onto a glassy carbon electrode with a diameter of 5 mm, controlling the metal loading at 20 μg cm⁻¹. -2 After being slowly dried at room temperature, it was used as a working electrode for electrochemical testing.

[0051] Electrochemical tests were conducted using a Chi 760E electrochemical workstation in a five-cell electrochemical cell equipped with a three-electrode system. A carbon rod was used as the counter electrode, and a mercury / mercury oxide electrode was used as the reference electrode for alkaline testing. The electrolyte for alkaline testing was a 0.1 M KOH aqueous solution. The electrolyte was saturated with nitrogen or hydrogen for 30 min before testing, and this saturation was continuously introduced during the testing process.

[0052] Polarization curves were measured using linear sweep voltammetry (LSV) at a scan rate of 2 mV / s. -1 Prior to this test, the working electrode was first set at 200 mV s. -1 The scanning speed is between -0.1 and -0.3 V, and the scan is repeated 5 times.

[0053] The alkaline hydroxide LSV curves of the samples in Example 1, Comparative Example 1, and Comparative Example 2 are as follows: Figure 5 As shown. By Figure 5 It can be seen that, compared with the insufficient alkaline hydroxide stability of Comparative Example 1 and the poor alkaline hydroxide kinetics of Comparative Example 2, the palladium nanoclusters / amorphous ruthenium nanosheets prepared in Example 1 exhibit excellent hydroxide kinetics and outstanding stability. Even at a high potential of 0.5 V, its performance did not show significant degradation.

[0054] Figure 6 The figure shows the 160-h hydrogen peroxide stability test curves of the palladium nanoclusters / amorphous ruthenium nanosheets prepared in Example 1. Figure 6 As can be seen, the performance of palladium nanoclusters / amorphous ruthenium nanosheets in continuously catalyzing alkaline hydrogen oxidation reaction at a potential of 0.25 V for 160 h did not show significant degradation, indicating the excellent durability of the catalyst.

[0055] Figure 7 The results of the CO toxicity test on the hydroxide reaction of Example 1 and Comparative Example 2 in 0.1 M KOH (saturated H2 / 1000 ppm CO) solution are shown. It can be seen that the introduction of amorphous ruthenium nanosheets significantly enhances the CO poisoning resistance of palladium nanoclusters.

[0056] The above description is merely a preferred embodiment of the present invention and is not intended to limit the invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.

Claims

1. A ruthenium-based composite nanomaterial, characterized in that, It uses amorphous ruthenium nanosheets as a carrier to load metal nanoclusters; The metal is Pd, Pt, Ir or Rh.

2. The ruthenium-based composite nanomaterial as described in claim 1, characterized in that, Based on the total mass of ruthenium-based composite nanomaterials, the proportion of metal nanoclusters is 0.5 wt%-30 wt%.

3. The ruthenium-based composite nanomaterial as described in claim 1, characterized in that, The size of the metal nanoclusters is 2~5nm.

4. The method for preparing the ruthenium-based composite nanomaterial according to any one of claims 1 to 3, characterized in that, Includes the following steps: (1) Disperse ruthenium acetylacetone salt and potassium bromide in an aqueous ethanol solution, mix them evenly, and then remove the solvent to obtain the precursor material; (2) After calcining the precursor material in an oxygen-containing environment, it was kept warm in a hydrogen-argon mixed gas, washed, frozen in liquid nitrogen and freeze-dried to obtain amorphous ruthenium nanosheets; (3) Amorphous ruthenium nanosheets are dispersed in ethylene glycol solution, salts containing Pd, Pt, Ir or Rh are added, and after mixing evenly, heat treatment is performed. The solid is collected by solid-liquid separation, washed, frozen in liquid nitrogen and freeze-dried to obtain ruthenium-based composite nanomaterials.

5. The preparation method according to claim 4, characterized in that, In step (1), the molar ratio of ruthenium acetylacetonate to potassium bromide is 1:(6~8). Alternatively, in step (1), the volume ratio of ethanol to water in the ethanol-water solution is (6~8):1; Alternatively, in step (1), the concentration of ruthenium acetylacetonate in the aqueous ethanol solution is 6-8 mmol / L.

6. The preparation method according to claim 4, characterized in that, In step (1), the temperature for solvent removal is 40~50℃; Alternatively, in step (2), the aerobic environment is air; Alternatively, in step (2), the calcination temperature is 260~350 ℃ and the calcination time is 1-4 h.

7. The preparation method according to claim 4, characterized in that, In step (2), the volume fraction of hydrogen in the hydrogen-argon mixture is 8-12%, preferably 10%; Alternatively, in step (2), the temperature for heat preservation is 100~200 ℃ and the heat preservation time is 0.5~2 h.

8. The preparation method according to claim 4, characterized in that, In step (3), the heat treatment temperature is 75~200 ℃; the heat treatment time is 1~3 h.

9. The application of the ruthenium-based composite nanomaterial according to any one of claims 1 to 3 or the ruthenium-based composite nanomaterial prepared by the preparation method according to any one of claims 4 to 8 in the catalysis of hydrogen oxidation in an alkaline environment.

10. A fuel cell, characterized in that, It includes a cathode, an anode, and a diaphragm, wherein the anode is a ruthenium-based composite nanomaterial according to any one of claims 1 to 3 or a ruthenium-based composite nanomaterial prepared by the preparation method according to any one of claims 4 to 8.